Qualidade da água para consumo humano ofertada em escolas e comunidades rurais da região central do Rio Grande do Sul - Casali, Carlos Alberto (2008)
In rural areas, including rural schools, the water intended for human consumption may not have quality, due to problems in their capture and storage, leaving the rural population in the mercy of contamination and diseases of hydric veiculation. This work has the follows objectives: a) achieve a diagnosis of the quality of water for human consumption in schools and rural communities of the Central Region of Rio Grande do Sul, b) verify its relationship with the system of water supply used, their level of maintenance, the hygienic situation of the establishments and the existence of point and diffuse sources of pollution. To do so, it was selected up the municipalities of Jaguari, São Francisco de Assis, Santa Maria, São Sepé and Tupanciretã, therefore include different agricultural and social realities. In these municipalities, were sampled 34 schools in rural communities which do not participate in programmes official tracking of water quality. There were, within one year, three collections of water, which was characterized in chemistry, physics, organoleptic and biologically. Moreover, the points of collection were characterized environmentally through photographs and a spreadsheet. Of the 34 points monitored, 64.7% are supplied by well tubular, has 35.3% of surface water catchment and none has treatment of water and sewage. São Francisco de Assis is the council that sets water quality with greater commitment, because of four of the eight schools and rural communities is supplied by surface water, come from sources and wells poorly constructed. However, the municipality Tupanciretã presented the highest number of points with drinking water of good quality, because of six of the seven points are supplied by wells and by tubular perform and had annual cleaning of the water reservoirs. In all monitored points 73.5% are supplied through water in disagreement of the limits established by Order Nº 518/2004 of the Ministry of Health for the parameters evaluated. Thus, it appears that most of the users of schools and rural communities of the Central Region of RS are consuming water out of the patterns of drinking stipulated by Brazilian legislation and the improvement of water quality offered depends on dissemination of technologies for sanitation and the efficient use of methodologies for the environmental education of the residents of rural areas.